The mediating role of knowledge sharing in the relationship between human capital, structural capital, spiritual capital, and MSMEs innovation - Nurunnisa Ayung Prinika Sugianto; Bima Cinintya Pratama; Eko Hariyanto; Ira Hapsari (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2024)
Purpose — This research aims to illuminate the influence of human capital, structural capital, and spiritual capital on innovation, mediated by knowledge sharing.Method — This research employs a quantitative methodology. It involves gathering data through a questionnaire that utilizes convenience sampling, focusing on 200 MSME operators across Banyumas, Brebes, and Cilacap. The statistical analysis utilizes Partial Least Square Structural Equation Modeling (PLS-SEM).Result — We found that human capital, structural capital, and spiritual capital directly impact innovation in MSMEs. Furthermore, we observe that knowledge sharing functions as a mediator in MSMEs innovation.Contribution — The study extends previous research, adding knowledge sharing as a mediating variable to explore its role in the nexus among human capital, structural capital, spiritual capital, and MSMEs innovation.